2016
DOI: 10.1096/fj.201600615r
|View full text |Cite
|
Sign up to set email alerts
|

Netrin‐1 and its receptor Unc5b are novel targets for the treatment of inflammatory arthritis

Abstract: Rheumatoid arthritis is an autoimmune disease that is characterized by chronic inflammation and destruction of joints. Netrin-1, a chemorepulsant, laminin-like matrix protein, promotes inflammation by preventing macrophage egress from inflamed sites and is required for osteoclast differentiation. We asked whether blockade of Netrin-1 or its receptors [Unc5b and DCC (deleted in colorectal carcinoma)] may be useful therapeutic targets for treatment of inflammatory arthritis. Arthritis was induced in 8-wk-old C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
(66 reference statements)
3
35
0
2
Order By: Relevance
“…In addition to the regulation of immune cell migration, Netrin‐1 was shown to regulate the inflammatory response of macrophages through suppression of COX‐2–mediated PGE2 production and also promote macrophage reprogramming to induce inflammation resolution . Furthermore, Netrin‐1 binding with its receptor Unc5b takes part in osteoclast biology and thus suggested as a therapeutic target for inflammatory bone destructive diseases . In this study, Netrin‐1 and its receptor Unc5b were detected in all samples.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to the regulation of immune cell migration, Netrin‐1 was shown to regulate the inflammatory response of macrophages through suppression of COX‐2–mediated PGE2 production and also promote macrophage reprogramming to induce inflammation resolution . Furthermore, Netrin‐1 binding with its receptor Unc5b takes part in osteoclast biology and thus suggested as a therapeutic target for inflammatory bone destructive diseases . In this study, Netrin‐1 and its receptor Unc5b were detected in all samples.…”
Section: Discussionmentioning
confidence: 56%
“…Maruyama, et al determined high levels of Netrin‐1 in the synovial fluid of rheumatoid arthritis patients and Netrin‐1 treatment attenuated bone erosion. In line with, blockade of Netrin‐1/Unc5b prevented bone destruction and reduced the severity of arthritis . Rosenberger, et al reported that Netrin‐1 was strongly induced by hypoxia and pretreatment with exogenous Netrin‐1 abolished the hypoxia‐dependent increases in plasma cytokine concentrations and PMN numbers into the colon, lungs, and kidneys, thus ameliorate mucosal inflammation.…”
Section: Discussionmentioning
confidence: 67%
“…After sacrifice, long bones (n ¼ 10 each treatment) were fixed in 70% ethanol and prepared for high-resolution mCT as previously described. (21) Briefly, analyses were performed in Skyscan 1172 mCT (Bruker, WI, USA) using the following imaging parameters: 60 kV, 167 uA, 9.7 micron pixel size, 2000 Â 1332 matrix, 0.3-degree rotation steps, six averages, movement correction of 10, 0.5-mm Al filter. Images were reconstructed using the Skyscan NRECON software (histogram range 0 to 0.085, beam-hardening correction of 40, Gaussian smoothing (factor 1), ring artifact correction of 8).…”
Section: Micro-x-ray Computed Tomography Analysismentioning
confidence: 99%
“…Interestingly, Unc5 family netrin-1 receptors were abundant in BMMs ( Supporting Fig. 2), and numerous studies have confirmed the importance of Unc5b (24)(25)(26)(27) and RANK (39)(40)(41) in OC formation. We thus examined the expression levels of these receptors (Unc5b, RANK, integrin aV, and integrin b3) in OCs from control and Myo10 m/m mice (Fig.…”
Section: Similar Osteoporotic Deficit With Elevated Bone Resorption Amentioning
confidence: 77%
“…In addition, the blockade of netrin-1 or Unc5b by monoclonal antibodies also decreases the number of OCs, preventing bone destruction and reducing the severity of K/BxN serum transfer-induced arthritis. (25) The anti-OCs and bone protective effects by anti-Netrin-1 or anti-Unc5b antibodies are also observable in a murine model of multiple myeloma. (26) Moreover, netrin-1 and Unc5b expression are increased during OC differentiation, and blockade of netrin-1 or Unc5b prevents OC differentiation from both murine and human precursors.…”
Section: Introductionmentioning
confidence: 99%